Relationship Of Information And Mothersâ EducationToward Children Mental Retardation Treatment In Primary Disability School (Sdlb) Labuy City Banda Aceh - Husna, Asmaul (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2015)
1-3% of the Indonesia population range suffer mental retardation, the incidence is difficult to know because the mental retardation sometimes not recognized until the mid-age children where retardasinya still being float. The highest incidence come about children aged 10 to 14 years. Mental Retardation blew to men about 1,5 times more than women. This research aim to find out the relationship of information and mothersâ education toward children mental retardation treatment in Primary Disability School. This research is Analytic survey, that usedÂ  cross-sectional approach, population in this study were all mothers of children with mental retardation Primary Disability School (SDLB) in Labuy Banda Aceh. The result of this research is a significant relationship between the information of children with mental retardation treatment in Primary Disability School (SDLB) in Labuy Banda Aceh 2014 (p value = 0.040). There is a significant relationship between the education of children with mental retardation treatment in Primary Disability School (SDLB) in Labuy Banda Aceh 2014 (p value = 0,011).